Shared services in Brazilian local government: Urban development in small counties. (12th April 2019) - Consciência Silvestre, Hugo; Cunha Marques, Rui; Dollery, Brian; Moraes Correia, Aldenisio
Abstract : In this article we break new ground by investigating cooperative agreements in urban development services, which include urban development, housing and sanitation for small local governments in Brazil (i.e., those with fewer than 20, 000 residents in 2013–15). We find that public expenditure on urban development can be explained by both horizontal (intermunicipal cooperation) and vertical (public–public partnerships) cooperation. Regarding the impact of public sector cooperation on public expenditure, our results show that housing and sanitation services are less costly under intermunicipal cooperation. By contrast, urban development services are less costly when local authorities do not cooperate with other public entities. For public–public partnerships (with the state or federal government) cooperation leads to an increase in public funding, which implies that cooperative agreements might not lead to lower public expenditure. The findings in this article provide useful empirical insights into the administrative reorganization of Brazilian local government.